Structural basis for vitamin D receptor agonism by novel non‐secosteroidal ligands. Issue 7 (24th February 2013) - Asano, Lisa; Ito, Ichiaki; Kuwabara, Naoyuki; Waku, Tsuyoshi; Yanagisawa, Junn; Miyachi, Hiroyuki; Shimizu, Toshiyuki
Abstract : Non‐secosteroidal ligands for vitamin D receptor (VDR) have been developed for the agonist with non‐calcemic profiles. Here, we provide the structural mechanism of VDR agonism by novel non‐secosteroidal ligands. All ligands had the similar efficacy, while two had the higher potency. Crystallographic analyses revealed that all ligands interacted with helix H10 and the loop between helices H6 and H7 in a similar manner, but also that the two ligands with higher potency had different interaction modes. This study suggests that distinct ligand potency depend upon differences in the formation and rearrangement of hydrogen‐bond networks induced by each ligand. Abstract : ► We developed four novel non‐secosteroidal ligands. ► The crystal structures of VDR in complex with these ligands were determined. ► The two ligands acted as more potent VDR ligands than others. ► The binding modes are different depending on their potency.